(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Colonialism refers to the process of one country establishing political, economic and cultural control over another country or territory outside its borders. It also includes the dominance of the colonial power over the local population of the colonial area. Often the goal is to exploit resources and increase the wealth and influence of the colonizers. The colonial period began in the 15th century and lasted until the middle of the 20th century. Economic interests were among the main motivations for colonial expansion. Because the European powers believed that it was their duty to civilize the world and convert the native population to Christianity. It also involved European confrontations, notably Britain, France and the Dutch. Until the 19th century, the British Empire was established as the largest empire in history, which covered almost a quarter of the world’s area. Colonialism had a lasting impact on India as well as the rest of the world. On the one hand, it has facilitated the spread of technology, education and cultural exchange, but on the other hand, it has caused immense suffering to the local population. Consequently, in the mid-20th century, a combination of Hindustan nationalist movements, anti-colonial resistance and geopolitical changes contributed to the decline of colonialism. However, World War I and World War II also played a vital role in the movement. That was the reason to gain independence after World War II for many colonies and thus.